Can Maquila Booms Reduce Poverty? Evidence from Honduras - de Hoyos, Rafael E. (Washington, DC: World Bank, 2012)
This paper identifies and estimates the strength of the reduction in poverty linked to improved opportunities for women in the expanding maquila sector. A simulation exercise shows that, at a given point in time, poverty in Honduras would have been 1.5 percentage points higher had the maquila sector not existed. Of this increase in poverty, 0.35 percentage points is attributable to the wage premium paid to maquila workers, 0.1 percentage points to the wage premium received by women in the maquila sector, and 1 percentage point to employment creation. Given that female maquila workers represent only 1.1 percent of the active population in Honduras, this contribution to poverty reduction is significant.